Types and ways of complex phrases formation (Eurasian Journal of Philology Science and Education, 2019)
This article is dedicated to the discussion about structures, features and meanings of the complexphrases in Kazakh language. The author analyzed a lot of scientific works and conclusions about thecomplex phrases, including phraseological units and proposed to divide the complex phrases accordingto patterns of structure in linguistics. As a purpose of the above the researches of some authors wereconsidered and taken as a basis. The research of T. Sayrambaev «Complicated phrases in the modern Kazakh language», where discussed in detail the features of the phrase, is taken as basis. The article also hasthe comparative analysis of compound phrase in linguistics, with particular attention to the distinctivefeatures between the compound phrases and compound words. In addition, the morphological changeof the parts of speech is designated through the forms of connection in phrase and the importance of partof sentence through the phrase`s formation.Also the parts of speech are indicated as basic elements of the phrase structure and the special attention is paid to the problems of differences between types of phrases in the article. It is noted, thatdifficulties in defining the role of the individual words without meaning and words with meanings byeach member of the parts of speech with the separate parts of speech, its morphological differences, thestructural system and the properties of the connection. Thus the hallmark of compound words, etymonfrom parts of phrase is defined.